2019
DOI: 10.1101/649335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cohesin promotes stochastic domain intermingling to ensure proper regulation of boundary-proximal genes

Abstract: The mammalian genome has been segmented into thousands of topologically associated domains (TADs) based on chromosome conformation capture studies, such as Hi-C.TADs have been proposed to act as insulated neighborhoods, spatially sequestering and insulating the enclosed genes and regulatory elements through self-association and chromatin looping. Recent results indicate that inter-TAD interactions can also occur. However, the nature, extent, and function of these inter-TAD interactions remains unclear. Here, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…Notably, most of these interactions are retained throughout interphase, and a subset are also observed in mitosis, in contrast to the largely transient interactions between cis-regulatory regions observed in early G1 that may reflect the A/B compartment signal . This finding is consistent with observations that cohesin depletion abrogates TADs but not all chromosomal interactions (El Khattabi et al, 2019;Gassler et al, 2017;Rao et al, 2017;Schwarzer et al, 2017;Wutz et al, 2017)is also in line with evidence of cohesin-independent fine-scale chromosomal topology obtained in recent microscopy studies (Bintu et al, 2018;Luppino et al, 2019). These cohesin-independent contacts are presumably separate in nature from the well-characterised A/B compartment structure that is also independent of architectural proteins (Nora et al, 2017;Nuebler et al, 2018;Rao et al, 2017;Wutz et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, most of these interactions are retained throughout interphase, and a subset are also observed in mitosis, in contrast to the largely transient interactions between cis-regulatory regions observed in early G1 that may reflect the A/B compartment signal . This finding is consistent with observations that cohesin depletion abrogates TADs but not all chromosomal interactions (El Khattabi et al, 2019;Gassler et al, 2017;Rao et al, 2017;Schwarzer et al, 2017;Wutz et al, 2017)is also in line with evidence of cohesin-independent fine-scale chromosomal topology obtained in recent microscopy studies (Bintu et al, 2018;Luppino et al, 2019). These cohesin-independent contacts are presumably separate in nature from the well-characterised A/B compartment structure that is also independent of architectural proteins (Nora et al, 2017;Nuebler et al, 2018;Rao et al, 2017;Wutz et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…However, super-resolution imaging and chromatin tracing revealed a more complex picture of TAD architecture in single cells with highly variable boundaries that persisted after cohesin depletion 48 . More recent studies also revealed a similar picture in which neighboring TADs intermingled with each other extensively 76 . Even more surprisingly, depletion of cohesin lead to a reduction in the intermingling between neighboring TADs rather than inducing ectopic interactions as would be expected from the global loss of TADs observed in Hi-C 76 .…”
Section: Mechanisms That Organize the Genomementioning
confidence: 59%
“…More recent studies also revealed a similar picture in which neighboring TADs intermingled with each other extensively 76 . Even more surprisingly, depletion of cohesin lead to a reduction in the intermingling between neighboring TADs rather than inducing ectopic interactions as would be expected from the global loss of TADs observed in Hi-C 76 . Overall, architectural proteins like cohesin and CTCF do seem to play an important role in genome organization, however the precise principles of how these proteins cooperate to organize the genome are still being uncovered.…”
Section: Mechanisms That Organize the Genomementioning
confidence: 59%
See 1 more Smart Citation